EFEKTIFITAS PENGGUNAAN METODE FONETIK UNTUK MENINGKATKAN KEMAMPUAN PENGUCAPAN KONSONAN / R/ PADA ANAK TUNARUNGU SEDANG KELAS I DI SLB CENTER PAYAKUMBUH - Laila Kamilaturahmi, Yarmis Hasan, Kasiyati (Universitas Negeri Padang, 2013)
This research is motivated by problems found by researchers at SLB Payakumbuh N Center, a first class deaf children with problems in the second half, especially in pronunciation pronunciation consonant / r /. After holding asesment further against pronunciation consonant / r /, it showed that the child has a problem in pronunciation consonant / r /. This study aims to prove the effectiveness of the use of methods to improve pronunciation phonetic consonant / r / deaf children were class I in SLB N Center Payakumbuh. This research Single Subject Research approach, with ABA design and data analysis techniques using visual analysis chart. Subject is deaf child class I trained pronounce consonants / r / by using the phonetic method. Measurement using a variable percentage of how many words can be spoken child. The result shows that the method is effective in improving the ability of Phonetic pronunciation consonant / r / Deaf child class I SLB N Center Payakumbuh. Observations were made ​​with three sessions: the first session before granted intervention baseline (A1) is performed five times of observation, the percentage of the child's ability in this condition lies in the range of 0% and 20%. Second, the intervention sessions (B) by using the method of Phonetics, observations were made ​​as much as ten times, the percentage of the child's ability lies in the range of 20%, 40%, 60% and 80% on the third baseline session (A2) performed four times of observation, the obtained results child's ability in pronunciation consonant / r / increases the child lies in the range of 40% to 80%. Based on these results we can conclude the method is effective in improving the ability of Phonetic pronunciation consonant / r / in children with hearing impairment were class I in SLB N Center Payakumbuh. Suggested the teachers should be able to use the method of Phonetics in pronunciation training deaf children.